Laboratory manual for physical chemistry / Noraini Hamzah, Mohd Azizi Nawawi and Hairul Amani Abdul Hamid - Hamzah, Noraini; Abdul Hamid, Hairul Amani; Nawaw, Mohd Azizi (UiTM Press, 2025)
Physical chemistry is an essential branch of chemistry as it explores other branches of chemistry including inorganic, organic, biochemistry, geochemistry, and chemical engineering. Physical chemistry uses physical principles, chemical principles, and mathematics to understand and explain the properties and processes that matter undergoes on a molecular and atomic level. Laboratory manual for physical chemistry is an essential tool to provide the hands-on practical experience needed for complete learning of the introductory physical chemistry course. It is written in an easily readable style for undergraduate students.